Optimization of Instant Beverage Powder Containing Propolis Extract Nanoliposomes - Mehdi Mirzazadeh; Hadiseh Bagheri; Fatemeh Rasi; Nasim Mirzazadeh; Zahra Alam; Sahar Akhavan-Mahdavi (International Journal of Food Science)
Propolis is a natural resinous complex mixture produced by honeybees that contain various bioactive compounds. However, these bioactive compounds are chemically unstable and their absorption in the gastrointestinal tract is influenced by their solubility and stability. Encapsulation technology has been employed to increase their bioavailability and protect them against hostile conditions. Nanoliposomes are nanoscale lipid-based vesicles that can encapsulate various bioactive compounds, including propolis extracts. Therefore, in this study, propolis extract was encapsulated by nanoliposome technique and used in instant drink formulation. Nanoliposome characterization was done regarding particle size (255±0.21 nm), zeta potential (−37.6±1.14 mV), and encapsulation efficiency (73.71±0.94). Response surface methodology (RSM) was employed to determine the effect of nanoliposome concentration (0%–5%) on the beverage characteristics including Brix, acidity, hygroscopicity, water solubility index, total phenol content, total microbial count, and sensory analyses. RSM predicted that a 3.19% nanoliposome would provide the overall optimum region for preparing the beverage with the best characteristics. Therefore, nanoliposome containing propolis can be successfully used in the enrichment of the beverage formulation by maintaining the sensory characteristics and improving its quality.